Surface characterization of hollow fiber dialysis membranes used in artificial kidney. - Asmanrafat, Mehrdad. (University of Ottawa (Canada), 2002)
The internal and external surfaces of dialysis hollow fiber membranes were characterized by the combination of two techniques, e.g. contact angle measurement (CAM) and atomic force microscopy (AFM), aiming at the improvement of membrane biocompatibility. A number of surface properties including surface energy, roughness, pore size, and nodule size were evaluated. CAM studies were carried out by observing the liquid meniscus at the surfaces of hollow fibers. An imaging system equipped with a goniometer protractor and a video camera was developed for this purpose. AFM studies were also conducted at the internal surface of hollow fibers by cutting the fibers at an inclined angle. It was found that the contact angle depended not only on the polymeric material but also on the surface morphology including nodule size and roughness parameters. The theoretical prediction showed that the measured contact angle would be greater than the value intrinsic to the membrane material, and the prediction was confirmed by experimental data. It was also theorized that this behavior was the consequence of the formation of composite structures at the membrane surface.
Keywords: Engineering, Biomedical.